Gastric adenomas and their management in familial adenomatous polyposis - Martin, Isabel; Roos, Victorine H.; Anele, Chukwuemeka; Walton, Sarah-Jane; Cuthill, Victoria; Suzuki, Noriko; Bastiaansen, Barbara A.; Clark, Susan K.; von Roon, Alexander; Dekker, Evelien; Latchford, Andrew (Endoscopy, 2020)
Background Patients with familial adenomatous polyposis (FAP) are at increased risk of developing gastric adenomas. There is limited understanding of their clinical course and no consensus on management. We reviewed the management of gastric adenomas in patients with FAP from two centers.Methods Patients with FAP and histologically confirmed gastric adenomas were identified between 1997 and 2018. Patient demographics, adenoma characteristics, and management/surveillance outcomes were collected.Results Of 726 patients with FAP, 104 (14 %; 49 female) were diagnosed with gastric adenomas at a median age of 47 years (range 19 – 80). The median size of gastric adenomas was 6 mm (range 1.5 – 50); 64 (62 %) patients had adenomas located distally to the incisura. Five patients (5 %) had gastric adenomas demonstrating high-grade dysplasia (HGD) on initial diagnosis, distributed equally within the stomach. The risk of HGD was associated with adenoma size (P = 0.04). Of adenomas > 20 mm, 33 % contained HGD. Two patients had gastric cancer at initial gastric adenoma diagnosis. A total of 63 patients (61 %) underwent endoscopic therapy for gastric adenomas. Complications occurred in three patients (5 %) and two (3 %) had recurrence, all following piecemeal resection of large (30 – 50 mm) lesions. Three patients were diagnosed with gastric cancer at median follow-up of 66 months (range 66 – 115) after initial diagnosis. Conclusions We observed gastric adenomas in 14 % of patients with FAP. Of these, 5 % contained HGD; risk of HGD correlated with adenoma size. Endoscopic resection was feasible, with few complications and low recurrence rates, but did not completely eliminate the cancer risk.